2016
DOI: 10.1164/rccm.201510-2023oc
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Mortality and Major Adverse Cardiovascular Events in Sepsis Survivors. A Nationwide Population-based Study

Abstract: These data indicate that sepsis survivors had substantially increased risks of subsequent all-cause mortality and major adverse cardiovascular events at 1 year after discharge, which persisted for up to 5 years after discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
136
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(151 citation statements)
references
References 46 publications
10
136
2
1
Order By: Relevance
“…A recent controlled study showed that late excess mortality was higher in patients with 3 or more organ dysfunctions, even after adjusting for acute mortality differences [141]. Another recent study observed these [141] effects were significantly higher in male patients, younger patients, those with higher Charlson Comorbidity Index scores, those with higher numbers of organ failure, those admitted to intensive care units, those with shock, and those who required mechanical ventilatory support [142].…”
Section: What Are the Predictors Of Sepsis Long-term Morbidity And Momentioning
confidence: 99%
See 2 more Smart Citations
“…A recent controlled study showed that late excess mortality was higher in patients with 3 or more organ dysfunctions, even after adjusting for acute mortality differences [141]. Another recent study observed these [141] effects were significantly higher in male patients, younger patients, those with higher Charlson Comorbidity Index scores, those with higher numbers of organ failure, those admitted to intensive care units, those with shock, and those who required mechanical ventilatory support [142].…”
Section: What Are the Predictors Of Sepsis Long-term Morbidity And Momentioning
confidence: 99%
“…One study showed that mortality was increased, compared with matched non-hospitalized controls, non-septic infected hospitalized patients and patients admitted with sterile inflammatory conditions [141]. Another study demonstrated that septic patients had higher mortality than matched controls from the general population and subjects who were hospitalized for a non-septic cause [142]. Data from newer cohorts with appropriate controls have also shown that sepsis survivors have a higher risk of hospital readmission which is associated with an increased risk of death [143][144][145].…”
Section: Post-icumentioning
confidence: 99%
See 1 more Smart Citation
“…In the only population-based study investigating 1-year mortality and cause of death, Dekker et al observed that mortality increased with age and 25% of deaths were attributable to complications among 1924 patients who underwent stage I-III colorectal cancer resection in The Netherlands (Dekker et al, 2014). Furthermore, older patients may be at higher risk for septic complications, and there is increasing evidence that sepsis is associated with worse long-term survival following colorectal cancer surgery as well as an increased risk of cardiovascular events due to a sepsis-mediated systemic inflammatory response (Yende et al, 2014;Aquina et al, 2016a;Ou et al, 2016;Park et al, 2016). However, no similar studies to date have been performed in the United States.…”
mentioning
confidence: 99%
“…For the overall cohort, the median number of days in a healthcare facility doubled from 5 in the year prior to sepsis, to 10 in the year after sepsis—suggesting that the healthcare utilization in the year after sepsis is not merely a reflection of sepsis survivors’ age, co-morbidity burden, or propensity to use healthcare, but is also a reflection of new disability 5 and heightened risk for medical deterioration after sepsis, such as recurrent infections 1618 , acute renal failure 17 , aspiration 17,19 , and cardiovascular events 20,21 .…”
Section: Discussionmentioning
confidence: 99%